Florida Crop/Pest Management Profile: Mamey Sapote and Sapodilla - Mark A. Mossler; Olaf Norman Nesheim (EDIS, 2002)
This document is CIR 1414, one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2002.